Aspects to consider in causality assessment of safety signals: broadening the thought process - Hammad, Tarek A.; Afsar, Salman; McAvoy, Laura B.; Le Louet, Hervé (Frontiers in Drug Safety and Regulation, 2023)
In the field of drug safety, causality assessment aims to determine the level of plausibility of the relationship between an adverse event and exposure to a particular product. It is after the causality assessment process that we will be able to point out a product adverse reaction. While regulators often require pharmaceutical companies to use a structured approach for assessing the causality of their products, the available methods are challenged by a number of procedural differences, even when drawing from the same domain of elements. To mitigate these inconsistencies, as well as the additional challenges associated with incomplete information and differences in the application of clinical judgments at the individual case level, this paper proposes a holistic framework for causality assessment that utilizes a combination of expert judgment/global introspection, evidence-based medicine, and probabilistic method. The goal of the presented approach is to provide a guide of clues to causality reminding medical safety assessors to seek and examine all available streams of evidence in totality and to assess this evidence in a qualitative, structured way.